2006
DOI: 10.1177/0267659106073976
|View full text |Cite
|
Sign up to set email alerts
|

Effects of centrifugal and roller pumps on survival of autologous red cells in cardiopulmonary bypass surgery

Abstract: The 24-h post-transfusion survival values of autologous RBC, measured by the 51 disodium chromate/99m technetium double isotope procedure, were not significantly different, whether the roller pump or the centrifugal pump was used in the extracorporeal circuit using membrane oxygenators during cardiopulmonary surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 14 publications
2
41
0
2
Order By: Relevance
“…Some studies have indicated Unpaired 't' test was done for test of significance; NS =not significant, S= significant n = number of patients sublethal damage by CPB instead of complete destruction, where RBC exposed to certain uniform shear stresses for prolonged time show significant changes in their deformability without lysis 10 . One study showed that 15% of the RBC subjected to CPB were irreversibly damaged and removed during the 24 hour post-infusion period 11 . Therefore, beside hemodilution anemia, the observed lower TC of RBC and Hb% in patients following CPB-aided cardiac surgery may be, at least partly, due to excessive hemolysis because of mechanical trauma from CPB procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated Unpaired 't' test was done for test of significance; NS =not significant, S= significant n = number of patients sublethal damage by CPB instead of complete destruction, where RBC exposed to certain uniform shear stresses for prolonged time show significant changes in their deformability without lysis 10 . One study showed that 15% of the RBC subjected to CPB were irreversibly damaged and removed during the 24 hour post-infusion period 11 . Therefore, beside hemodilution anemia, the observed lower TC of RBC and Hb% in patients following CPB-aided cardiac surgery may be, at least partly, due to excessive hemolysis because of mechanical trauma from CPB procedure.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Cardiac surgery results in a postoperative systemic inflammatory response syndrome due to a variety of factors including surgical trauma, exposure of blood to the artificial surface of the bypass circuit, tissue hypoperfusion, hemolysis, hemodilution, blood transfusion, and hypothermia. [9][10][11][12] Inflammation is believed to play a key role in the pathophysiology of AKI after cardiac surgery with CPB. A number of proinflammatory pathways are activated during CPB and can lead to leukocyte extravasation, lipid peroxidation, renal medullary congestion, and tubular cell injury.…”
mentioning
confidence: 99%
“…During CPB, blood is exposed to nonphysiologic surfaces and shear forces, leading to cell lysis and release of free hemoglobin into the circulation. 11,12,20 Free hemoglobin is removed from the circulation through binding to CD163, 21 a scavenger receptor on the cell surface of monocytes and macrophages that is upregulated by glucocorticoids in multiple cell lines. [22][23][24] Hence, enhanced removal of free hemoglobin through upregulated CD163 represents a biologically plausible pathway through which glucocorticoids may decrease the incidence of CPB-associated AKI.…”
mentioning
confidence: 99%
“…Moreover, the highly reconfigurable model and the semiautomated simulation process extend the usefulness of the presented method to a wider range of applications. With recent independent studies failing to show any advantage in using centrifugal over roller pumps (3)(4)(5)(6) in shortterm assistance applications (less than 8 h), roller pumps are still commonly used in circulatory assist devices. Given the good consistency between the simulated results and the existing experimental data, the presented method displays promising potential to more effectively guide the development of improved roller pump systems which produce less mechanical damage to cells.…”
mentioning
confidence: 99%